Will Artificial Intelligence (AI) Make the School Principal Redundant? A Preliminary Discussion and Future Prospects - Turgut Karakose (Educational Process: International Journal)
Background/purpose. Developments in the world of Artificial Intelligence (AI) is full steam ahead in the wake of the fourth industrial revolution. One of the hot discussions over the exponential advancement of AI has been whether this ability of machines to accomplish tasks that require human intelligence could take over the roles of humans in the workplace and make the human workforce redundant. The field of education was no exception since AI technologies have made significant inroads into the realm of education.